PENGARUH KEPALA SEKOLAH SEBAGAI LEADER DAN PEMBERIAN MOTIVASI KERJA TERHADAP DISIPLIN KERJA GURU SD - Uray Hartini; Uray Husna; Masluyah Masluyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2017)
AbstractTeacher work performance is one of the faktors that affect quality of education.        Ateacher is expected to continously improve his/her work performance since one of determinants of educational succsess in operational level is work performance of teacher. Emperical data demonstrate that low quality of education is reflekted by low quality of teacher work performance. The findings indicate that (1) headmaster leadership (X1) has significant influence on teacher work performance (Y) as Beta (b1) of 0.308 = 30.80%, 2) work motivation (X2) has influenced significanty on teacher work performance (Y) since Beta (B1) amount 0.311 = 31.10%; 3) head master leadership  (X1) and work  motivation (X2) have contributed simultaneously to work (Y) as value of R square amount to 0.332 or 33.20%. F test result of  ANOVA output with multiple linear regression analysis demonstrate  Fcount> Ftable (15,683>3,136). Implication of this study ecompass, (1) public elementary school teachers in Sambas sub-district require heigtening their work performance for profesional development,              (2) headmaster need to inspire teachers to develop their profesionalism by persistently providing guidance, monotoring, supervision, training and appreciation.  Keywords: Headmaster Leadership, Work Motivation, Teacher Work Permonmance